2021
DOI: 10.1016/j.chest.2021.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Early Management Practices in Moderate-to-Severe ARDS in the United States

Abstract: BACKGROUND: Although specific interventions previously demonstrated benefit in patients with the ARDS, use of these interventions is inconsistent, and patient mortality remains high. The impact of variability in center management practices on ARDS mortality rates remains unknown.RESEARCH QUESTION: What is the impact of treatment variability on mortality in patients with moderate to severe ARDS in the United States? STUDY DESIGN AND METHODS: We conducted a multicenter, observational cohort study of mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 37 publications
2
43
1
Order By: Relevance
“…Practice variation has recently been described in non-COVID ARDS, showing variance in tidal volume and ventilation pressures ( 7 ). We have now shown practice variation is still clearly demonstrable in a relatively homogenous underlying disease mechanism that shows evolvement over the duration of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Practice variation has recently been described in non-COVID ARDS, showing variance in tidal volume and ventilation pressures ( 7 ). We have now shown practice variation is still clearly demonstrable in a relatively homogenous underlying disease mechanism that shows evolvement over the duration of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reduced sleep quality is common in the ICU [ 48 ], and associated with delirium [ 49 ]. A quality improvement process designed to feasibly promote sleep in critical care has been associated with reductions in night-time noise levels, delirium, and coma [ 50 52 ]. This process may be conducted stepwise, beginning with disturbance reduction, moving to non-pharmacological methods, and then adding pharmacological aid for those patients whom did not show sleep improvement after the first two stages [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early prone positioning has been shown to reduce mortality in patients with moderate-to-severe acute respiratory distress syndrome (ARDS) in a randomized controlled trial (1) and meta-analyses (2, 3), and is recommended in patients with ARDS by multiple guidelines (4, 5). However, prior to the COVID-19 pandemic, large multinational studies showed that proning was only used in 6–14% of patients with ARDS overall and in 16–33% of those with severe ARDS (6–9). Reasons for low adoption have included under-recognition of ARDS by clinicians (10, 11), a view of proning as rescue therapy (7, 12), clinician preference for other adjunctive interventions (12), and a presumption that proning is labor intensive (12, 13).…”
mentioning
confidence: 99%